2024
DOI: 10.1186/s12903-023-03675-8
|View full text |Cite
|
Sign up to set email alerts
|

Faculty of sports science students, physical education teachers, and athletes’ level of knowledge and attitude about mouthguards

Aslı Soğukpınar Önsüren,
Hüseyin Eroğlu,
Cemil Aksoy

Abstract: Objectives Traumatic dental injury occurs during sports competitions, training, and practice and can be prevented by the use of mouthguards. For this reason, this study aimed to evaluate the knowledge and attitudes of sports science faculty students, physical education teachers, and athletes about mouthguards. Methods Five hundred thirty-two participants were reached via social media. In the questionnaire consisting of 20 questions, questions about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…There is considerable debate about how the use of mouthguards affects an athlete's performance [ [11] , [12] , [13] , [14] ]. Some research that includes clinical studies and meta-analyses shows that personalized MTs do not negatively affect the athlete's performance, and in some cases their performance even improves [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. However, other authors have reported on athletes who have stopped using MTs due to discomfort when wearing them, and who have experienced difficulties in breathing, speaking, and drinking [ [27] , [28] , [29] ].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable debate about how the use of mouthguards affects an athlete's performance [ [11] , [12] , [13] , [14] ]. Some research that includes clinical studies and meta-analyses shows that personalized MTs do not negatively affect the athlete's performance, and in some cases their performance even improves [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. However, other authors have reported on athletes who have stopped using MTs due to discomfort when wearing them, and who have experienced difficulties in breathing, speaking, and drinking [ [27] , [28] , [29] ].…”
Section: Introductionmentioning
confidence: 99%